Compressive sensing-based channel estimation schemes for wideband millimeter wave wireless communication systems - Oyerinde, Olutayo O.; Flizikowski, Adam; Marciniak, Tomasz (Computers & electrical engineering, 2022)
•Millimeter (mm) Wave Massive MIMO communication systems with both hybrid precoder-combiner structure and low-bit resolution analog-to-digital converters (ADCs).•Projection-based Orthogonal Matching Pursuit (POMP)-based channel estimator.•Predictive Orthogonal Least Squares (POLS)-based channel estimator.•Determination of the approximate number of bits that result in optimum performances of the channel estimators in mm-Wave Massive MIMO communication systems. The introduction of both hybrid precoder-combiner structure and low-bit resolution analog-to-digital converters (ADCs) makes channel estimation in millimeter (mm) Wave Massive MIMO systems to be challenging. In the literature, several channel estimation schemes presented focus on narrowband channels. However, few works are found to be presented for the case of wideband channels for this system. In this paper, two new channel estimation techniques are proposed with the first scheme based on the Projection-based Orthogonal Matching Pursuit (POMP) algorithm. The second estimation scheme is based on the Predictive Orthogonal Least Squares (POLS) algorithm. In all the simulation results, POLS shows the best performance but with the highest computational complexity cost, with POMB exhibiting the next best performance with a lower computational complexity cost. In terms of compromise between performance and computational complexity cost, the proposed POLS-based channel estimator is the best estimator for the wideband mmWave Massive MIMO systems. Normalized Mean Squared Error (NMSE) performances of the proposed Projection-based Orthogonal Matching Pursuit (POMP)-based channel Estimator and Predictive Orthogonal Least Squares (POLS)-based channel estimator in comparison with some other channel estimators: number of receiver antenna Mr = 16, number of transmitter antenna, Mt = 128, and the number of quantization bits NQ = 8, [Display omitted]